The Effect of Institutional Ownership and Foreign Ownership on Company Performance - Mohammad Syafik (SEAN Institute, 2025)
Recently, the performance of mining companies has been sluggish, so it is necessary to know the cause of the decline in performance. The presence of ownership types is believed to play an important role in improving company performance. So this study aims to test the effect of institutional ownership and foreign ownership on company performance. The formulation of the research problem is (1) does institutional ownership have a positive effect on company performance? (2) does foreign ownership have a positive effect on company performance? The population used in this study is mining companies listed on the Indonesia Stock Exchange (IDX). The samples taken are mining companies listed on the IDX during the period 2016 to 2022. The total research sample is 253 observations determined through purposive sampling. The analysis method of this study uses multiple regression analysis techniques. Based on the results of the analysis, it can be concluded that institutional ownership has a positive effect on company performance with a significance value of 0.097, but foreign ownership has a significance value of 0.545 so that it does not affect company performance. This study can improve further research literature studies and can be used by company management in considering the right type of ownership in order to maximize company performance.